On the long-run equilibrium value of Tobin's average Q - Reiner Franke; Boyan Yanovski (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2016)
This note considers Tobin's average Q in a framework where firms finance investment by equities and debt. The determination of its long-run equilibrium value Q° is based on positing equality of the loan rate and, adjusted for a risk premium, the return on equities. Q° can thus be characterized as a ratio of two rates representing the somewhat modified interest costs and profits of the firms. The familiar benchmark value Q° = 1 obtains if another condition on the risk premium holds true, which may or may not be the case. An elementary numerical check demonstrates that possible deviations of Q° from unity are not overly dramatic.
Keywords: C02; D84; E12; E30; 330; Tobin's average Q; debt and equity financing; no-arbitrage condition; fundamentalist trader